Type of Mineral Deposits on Alteration Rocks using Petrography, X-Ray Fluorescence (XRF), and X-Ray Diffraction (XRD) Method in Geothermal Prospect in Tiouw Village, Maluku - Richard R Lokollo; Josephus Ronny Kelibulin (JPSE (Journal of Physical Science and Engineering), 2019)
Indonesia is a country with abundant geothermal energy potential. One of the locations that have potential geothermal energy sources is Tiouw Village, Saparua, Central Maluku. This study was conducted on the types of mineral deposits using the petrographic method, X-Ray Diffraction (XRD), and X-Ray Fluorescence (XRF). Based on the results of petrographic analysis and XRD, rock samples 1, 2, and 3 of Tiouw include andesite igneous rocks with propylitic alteration type. While sample 4 is dacite igneous rock with argillic alteration type. Each rock sample has a mineral set of kaolinite, chlorite, quartz, cristobalite, epidote, and plagioclase. The XRF results showed the highest chemical composition of SiO2, followed by Al2O3 and K2O. This mineral content can indicate the subsurface temperature of the geothermal field in the range of 200–300 ºC with varying salinity, pH close to neutral, and low permeability. This interpreted that the type of mineral deposits in Tiouw Village was high sulfidation epithermal deposits. DOI: http://dx.doi.org/10.17977/um024v4i22019p037